2016
DOI: 10.1001/jama.2016.0275
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Behavioral Interventions on Inappropriate Antibiotic Prescribing Among Primary Care Practices

Abstract: IMPORTANCE Interventions based on behavioral science might reduce inappropriate antibiotic prescribing. OBJECTIVE To assess effects of behavioral interventions and rates of inappropriate (not guideline-concordant) antibiotic prescribing during ambulatory visits for acute respiratory tract infections. DESIGN, SETTING, AND PARTICIPANTS Cluster randomized clinical trial conducted among 47 primary care practices in Boston and Los Angeles. Participants were 248 enrolled clinicians randomized to receive 0, 1, 2,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
769
9
7

Year Published

2016
2016
2020
2020

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 720 publications
(799 citation statements)
references
References 42 publications
14
769
9
7
Order By: Relevance
“…Furthermore, recent developments in behavioral economics provide examples of effective means to improve adherence with guideline‐recommended practice, such as a sufficient course of optimal medical therapy prior to device implant. For example, a recent study found that inappropriate antibiotic prescribing could be reduced by regular emails to physicians describing their performance as “top performing” or not 54. Electronic health records could facilitate these interventions by enabling automatic report generation for physicians and patients.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, recent developments in behavioral economics provide examples of effective means to improve adherence with guideline‐recommended practice, such as a sufficient course of optimal medical therapy prior to device implant. For example, a recent study found that inappropriate antibiotic prescribing could be reduced by regular emails to physicians describing their performance as “top performing” or not 54. Electronic health records could facilitate these interventions by enabling automatic report generation for physicians and patients.…”
Section: Discussionmentioning
confidence: 99%
“…[27][28][29] We extracted and combined sociodemographic and clinical information from the EHR with billing codes.…”
Section: Data Extractionmentioning
confidence: 99%
“…As part of a larger study, we invited 245 clinicians from 50 primary care practices in Boston and Los Angeles by e-mail to complete a web-based survey in June 2013 and January 2014, respectively (4,5). The full survey, of which the CRT was a part, generally took between 20 and 30 minutes to complete.…”
Section: Methodsmentioning
confidence: 99%